Controlling the Mobile Robot with the Pure Pursuit Algorithm to Tracking the Reference Path Sent from the Android Device - Top, Ahmet (My University, 2024)
Many of the equipment and machines we use in our everyday lives have changed due to major advancements in today's technology. Smartphones, which have made great progress especially in the last decade, perform many tasks in addition to interpersonal communication. Controlling robots, which are increasingly used in daily life and widely included in the literature, is one of these tasks. In this study, the pure pursuit algorithm was used to control the position of a non-holonomic differential drive mobile robot, and the path information to be tracked was received from an Android mobile device as a reference. An application design has been carried out for Android devices. The information for the path drawn here was transferred via the internet to a Google Spreadsheet. Coordinate information obtained from Google tables in MATLAB was separated as x and y axis information and entered into MATLAB/Simulink as waypoints of the pure pursuit algorithm and the position control of the robot was carried out. Error analysis was made by taking the differences between the reference path and the actual movement and the control performance was examined. Additionally, the effect of the approach distance value of the pure pursuit algorithm on the error is presented.
Keywords: Android application; Communication; Mobile robot; Pure pursuit algorithm